Analisis Kesulitan Literasi Dasar Siswa Kelas 2 Sekolah Dasar melalui Kajian Fonem-Grafem dan Teori Belajar - Ariska Dwi Aprilia; Yuris Indria Persada; Elvia Ardianti Ningrum; Revi Belva Armilda; Siti Romelah (Tarunateach: Journal of Elementary School, 2025)
Reading and writing skills are essential foundational abilities in primary education; however, not all students are able to master them optimally. This study aims to analyze basic literacy difficulties in a second-grade elementary student using a phoneme-grapheme approach and reviewed through cognitive, social, and behaviorist learning theories. This research employed a descriptive qualitative method with data collection techniques consisting of diagnostic tests and interviews. Five types of tests were administered to assess the student’s ability to recognize letter sounds, letter symbols, match sounds with letters, copy letters, and write letters from dictated sounds. The results showed that the student was able to recognize all letter sounds well but experienced significant difficulties in identifying letter symbols, matching sounds to letters, and writing them independently. The student demonstrated ability only with letters memorized by rote, particularly those found in their own name. Interviews also revealed that the student felt shy, lacked self-confidence, and showed low interest in reading and writing activities. These findings indicate that the student’s literacy difficulties stem from a weak phoneme-grapheme connection, compounded by cognitive limitations, minimal social interaction in learning, and low motivation. Therefore, an individualized, multisensory, and contextual learning approach is needed to support the student in developing literacy skills more effectively.